EXPERIMENTAL EVALUATION OF TRISHNAHARA (THIRST RELIEVING) PROPERTY OF TAKRABHEDA (BUTTERMILK) MENTIONED IN BHAVAPRAKASHA IN GREESHMARITU (AYUSHDHARA, 2020)
Takra is one of the important Paniya (drinks) in Indian culture. It is common drink used abundantly especially during the summer season. The main reason for its ample usage as a drink during summer might be the sudden relief it provides to the thirst and fatigue due to extreme heat. Literature review on the Ayurvedic concept of Takra shows it possesses Ushna Veerya and Amla Vipaka, which in turn increases the Pitta inside the body and will leads to thirst rather than decreasing thirst especially in Greehma Ritu. Thus, there exist a paradox in the literature and practice. Thus a study was conducted to find out the Trishnahara property of Takrabheda in Greeshma Ritu.In the experiment total intake of water by each group after administering specific variety of buttermilk were calculated. The study was conducted during Greeshmaritu in wistar albino rats. Numbers of groups were six which included Ghola, Matita, Takra, Udasvit Caccika and Control. statistical analysis was done by ANOVA followed by Dunnet multiple comparison as post hoc test, if p